Assessing the impact of disasters on technology transfer under international economic law:The case of space-based technologies - Cristani, Federica (Lit verlag, 2022)
This Chapter focuses on the economic consequences of natural disasters for affected states, in particular as regards technology transfer, taking space-based technology transfer in the Arctic region as a case-study. Space-based technology have indeed become an important element of regional, national and local disaster risk reduction strategies: suffice to recall, among others, the use of remote sensing and geographic information systems tools for monitoring and mapping risks, as well as the role of space technology applications in early warning and monitoring of slow onset disasters. But what happens in case of transfer of space-based technologies? Do disasters impact such processes and which (international) instruments come into play? And what is the current situation in the Arctic region? This Chapter examines the relevant regulatory framework of reference at the international level, with a mapping of technology transfer provisions in international disaster law instruments, international economic law provisions on technology transfer applicable in the context of disaster-related situations and space law provisions applying in case of transfer of space-based technologies, with a special fous on the Arctic.